Phosphorescent Pt(ii) complexes bearing cyclometalated difluorophenylpyridinate and diphosphine building blocks. (19th December 2022) - Shahsavari, Hamid R.; Chamyani, Samira; Aghakhanpour, Reza Babadi; Dolatyari, Vahideh; Paziresh, Sareh
Abstract : Mononuclear and binuclear cycloplatinated complexes with a variety of biphosphine ligands were investigated for their luminescent characteristics. Abstract : Two distinct categories of cycloplatinated(ii ) complexes [Pt(dfppy)(P^P)]Cl, 2, and [Pt2 Cl2 (dfppy)2 (μ-P^P)], 3, where dfppy = 2-(2, 4-difluorophenyl)pyridinate, P^P = bis(diphenylphosphino)methane (dppm), 1, 2-bis(diphenylphosphino)ethane (dppe) and 1, 2-bis(diphenylphosphino)benzene (dppbz), were synthesized and characterized. These compounds were photophysically investigated, and their absorption and emission spectra were recorded under different conditions. Bright green and bluish green emissions were observed for the complexes with mostly well-structured emission bands ( 3 ILCT/ 3 MLCT for the mononuclear and 3 ILCT/ 3 MLCT/ 3 XLCT for the binuclear complexes, L = dfppy, X = Cl) in the range of 460–480 nm (solid and CH2 Cl2 fluid solution states, 298 and 77 K). Unexpectedly, due to the inter-molecular interactions, the complex [Pt(dfppy)(dppm)]Cl, 2a, shows a very weak emission in the solid state, whereas its ppy (2-phenylpyridinate) derivative has a bright green emission under the same conditions. The complexes [Pt(dfppy)(dppe)]Cl, 2b, and [Pt(dfppy)(dppbz)]Cl, 2c, in their solid form, exhibit strong emissions at room temperature that are significantly higher than those observed for their ppy counterparts. The binuclear complexes of [Pt2 Cl2 (dfppy)2 (μ-dppm)], 3a, and [Pt2 Cl2 (dfppy)2 (μ-dppe)], 3b, show "no emission" and "weak emission" in the solid state at 298 K, respectively. Finally, DFT (density functional theory) and TD-DFT (time-dependent DFT) calculations were used to support the obtained photophysical data.